Examining the relationship between the use of supermarkets and over-nutrition in Indonesia - Umberger, Wendy J.; He, Xiaobo; Minot, Nicholas; Toiba, Hery (Wiley, 2015)
This study examines the relationship between the use of modern food retailers and health outcomes using data from a survey of 1,180 urban households in Indonesia. The dependent variables include adult and child body‐mass index and the share of individuals overweight and obese. After controlling for individual and household characteristics and using standard and Lewbel instrumental variable approaches to control for unobservable characteristics, we do not find a statistically significant relationship between use of supermarkets and adult nutrition measures. On the other hand, there is mixed evidence for a negative effect of supermarkets on child nutrition, particularly for those in high‐income households.